A novel fragmented mitochondrial genome in the protist pathogen Toxoplasma gondii and related tissue coccidia - Namasivayam, Sivaranjani; Baptista, Rodrigo P.; Xiao, Wenyuan; Hall, Erica M.; Doggett, Joseph S.; Troell, Karin; Kissinger, Jessica C.

(untitled) (Genome Research, 2021)
Mitochondrial genome content and structure vary widely across the eukaryotic tree of life, with protists displaying extreme examples. Apicomplexan and dinoflagellate protists have evolved highly reduced mitochondrial genome sequences, mtDNA, consisting of only three cytochrome genes and fragmented rRNA genes. Here, we report the independent evolution of fragmented cytochrome genes in Toxoplasma and related tissue coccidia and evolution of a novel genome architecture consisting minimally of 21 sequence blocks (SBs) totaling 5.9 kb that exist as nonrandom concatemers. Single-molecule Nanopore reads consisting entirely of SBs ranging from 0.1 to 23.6 kb reveal both whole and fragmented cytochrome genes. Full-length cytochrome transcripts including a divergent coxIII are detected. The topology of the mitochondrial genome remains an enigma. Analysis of a cob point mutation reveals that homoplasmy of SBs is maintained. Tissue coccidia are important pathogens of man and animals, and the mitochondrion represents an important therapeutic target. The mtDNA sequence has been elucidated, but a definitive genome architecture remains elusive.